PSYCHOLOGICAL HEALTH OF PROFESSIONAL ATHLETES INVOLVED IN EXTREME SPORTS - A. V. Aleshicheva (Вестник Кемеровского государственного университета, 2016)
The subject of the present study was to investigate the psychological health of professional athletes engaged in extreme sports. The research objective was to determine the effect of extreme sports on the psychological health of professional athletes. The study involved 168 professional athletes who deal with auto racing, judo, karate, rock climbing, melee fighting and boxing. Among them 2 groups were formed: the study group (n = 80), which included professionals, and the control group (n = 87), consisting of athletes who have II or III sports categories. Diagnosis of the mental health and changes in the psyche of the athletes was performed 2 – 3 days before the competition. Quantitative data were processed by methods of mathematical statistics. The study group, in contrast to the control group, showed an increase in the degree of manifestation of personal qualities that are treated as negative. These qualities include: anxiety, frustration, depression, stiffness. It was discovered that the intensity and duration of physical and mental stress cause the emergence of increased somatic symptoms in professional athletes (feeling of pain in the joints, stomach, heart and other organs). Extreme conditions of sports activity lead to mental exhaustion, increase sensitivity to the crisis, cause growth of occupational stress and reduce the quality of life. The author diagnosed exacerbation of somatic symptoms, an increase in the subjective level of morbidity, increase in the degree of manifestation of social disfunction and deterioration of the social and psychological health of professional athletes. The primary factors negatively affecting the psyche of athletes can be postulated as professionalisation and commercialization of sport, which entail the growth of extreme loads, excessive physical and mental stress and a significant deterioration in social and psychological health of professional athletes.